2019
DOI: 10.24233/biov.5.2.2019.150
|View full text |Cite
|
Sign up to set email alerts
|

STUDY OF PRODUCTION AND VIABILITY COCOON OF Pontoscolex corethrurus FR.MULL AT VARIOUS CONCENTRATIONS OF CARBARYL INSECTICIDES

Abstract: Research on the Study of Cocoon Production and Viability of Pontoscolex corethrurus Fr. Mull at various concentrations of Karbaril insecticide was carried out in July to October 2019, at the Laboratory of Animal Physiology, Department of Biology, Faculty of Mathematics and Natural Sciences, Sriwijaya University, Inderalaya, Ogan Ilir, South Sumatra. This study aims to study the production of cocoon and viabiltas earthworm Pontoscolex corethrurus Fr. Mull at various concentrations of carbaryl insecticide as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Berdasarkan survei di beberapa pasar hewan di Indonesia, menunjukkan bahwa 90% hewan ternak sapi dan kerbau mengidap penyakit cacingan, Penyebab penyakit cacingan antara lain: konsumsi hijauan yang masih berembun dan tercemar vektor pembawa cacing (Nofyan et al, 2010). Penyakit yang disebabkan dari golongan Helminth atau golongan cacing yang menyerang sapi merupakan gangguan kesehatan utama yang mencapai 35% (Susanti dan Prabowo, 2013).…”
Section: Pendahuluanunclassified
“…Berdasarkan survei di beberapa pasar hewan di Indonesia, menunjukkan bahwa 90% hewan ternak sapi dan kerbau mengidap penyakit cacingan, Penyebab penyakit cacingan antara lain: konsumsi hijauan yang masih berembun dan tercemar vektor pembawa cacing (Nofyan et al, 2010). Penyakit yang disebabkan dari golongan Helminth atau golongan cacing yang menyerang sapi merupakan gangguan kesehatan utama yang mencapai 35% (Susanti dan Prabowo, 2013).…”
Section: Pendahuluanunclassified
“…According to [1], vermicompost is the result of fragmentation of organic matter by physical and chemical activity of earthworms mixed with the excrement they secrete which is rich in microbial living cells. Research [2], showed that in the decomposition process, earthworms have a higher ability compared to other soil organisms. According to [3], [4] organic fertilizer can be produced from worms which contain elements such as N, P, K, Ca, Mg, S and other nutrients that plants can need.…”
Section: Introductionmentioning
confidence: 99%